LEGAL REVIEW OF THE POSITION OF MEDIATION AS AN EFFORT TO RESOLVE CASES IN RELIGIOUS COURTS IN INDONESIA (ANALYSIS OF PERMA NUMBER 1 OF 2016) (STUDY IN SIBOLGA RELIGIOUS COURT) - Ari Ambrianti; Andoko, Andoko; Azhali Siregar (PT. Sinergi Legal Publisher, 2025)
The judicial system in Indonesia plays an important role in enforcing the law and providing legal certainty for the community. However, the lengthy litigation system and high costs often become obstacles in resolving disputes. Mediation as an alternative form of dispute resolution offers a faster, more efficient, and win-win solution. The Supreme Court has strengthened the role of mediation through various regulations, including Supreme Court Regulation (PERMA) Number 1 of 2016 concerning Mediation Procedures in Court. This regulation requires the parties to undergo mediation before proceeding to the litigation process, with the aim of reducing the burden of cases in court and encouraging more peaceful dispute resolution. This study focuses on the implementation of mediation in dispute resolution at the Sibolga Religious Court based on PERMA Number 1 of 2016. The results of the study indicate that although the regulation has been quite comprehensive, the implementation of mediation still faces various obstacles, such as the low success rate of mediation, lack of public understanding of the benefits of mediation, and limited number of competent mediators. Therefore, strategic efforts are needed, such as increasing the capacity of mediators, wider socialization to the community, and incentives for mediators who succeed in resolving cases. With these steps, the effectiveness of mediation in the Religious Court is expected to increase, so that dispute resolution can be faster, cheaper, and fairer.